The mortality rate of patients with open abdomen and contributing factors: three-year audit in a major academic trauma unit - van der Merwe, Estelle (My University, 2022)
Background Damage control surgery is a well-known and widely used approach in trauma. (1) An essential element of damage control surgery is the need to leave the abdomen open with a temporary closure device in place. An open abdomen carries complications, such as infections, enteric fistula and ventral hernia formation. These patients also have increased length of hospital and ICU stay, with increased morbidity and mortality. (2) This study aims to quantify the mortality rate of patients with an open abdomen and determine possible contributory factors to mortality. Secondary objectives were to determine factors influencing the decision to perform DCS and assess morbidity in the open abdomen patient: surgical site infection, hernia rate and entero-atmospheric fistula. Materials and Methods A retrospective review was conducted on 205 patients submitted to damage control surgery in the Charlotte Maxeke Johannesburg Academic Hospital Trauma Unit. Mortality rates were evaluated over a 24-hour, 7-day and 28-day period. Data were collected by filling a data collection sheet, including patients over a three-year period: 01 January 2016 to 31 December 2018. Results The study found a mortality rate of 26.8% for open abdomen patients, 34.5% within the first 24-hours, 40% in the 24-hours to 7-day, and 25.4% in the 8-day to 28-day periods. Statistically significant factors found to contribute to mortality were haemodynamic instability (p-value 0.003), hypothermia (p-value 0.047), coagulopathy (p-value 0.004), massive transfusion (p-value 0.003), vasopressor usage (p-value 0.008), and significant associated injuries (0.008). For survival analysis, pH, lactate, injury severity score (ISS), and systolic blood pressure BP reading, were found to correlate with the increased risk of mortality in patients with an open abdomen. Open abdomen patients were found to have multiple morbidities, of which enteroatmospheric fistula (EAF) was found in 7.3%, surgical site infection in 45.3% and ventral hernia in 10.24%. Conclusions Our data demonstrated that patients undergoing damage control surgery are at risk of mortality due to multiple contributing factors. The majority of patients demised within 24-hours to 7-days (40%). The most common morbidity associated with an open abdomen was surgical site infection (45,46%). Open abdomen management remains an appropriate management in critically ill patients but does carry a high risk of mortality and morbidity.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine Surgery to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021